The Principle of Good Faith in The Choice of Law of Foreign Direct Investment Contracts in Indonesia - Rizky Amalia; Hilda Yunita Sabrie; Widhayani Dian (Fiat Justisia: Jurnal Ilmu Hukum, 2018)
Applying the principle of good faith in the choice of law is one of the most common problems of international business contract, particularly in foreign direct investment contracts. The implementation of the principle of good faith in the choice of law increasingly reduced by the emergence of some problems in the investment contract, which of course, the most aggrieved entities are domestic investors who also host country. The choice of law has an important role in the contract because it concerns the interests of each of the parties, and the principle of good faith as a priority principle of international contract law should be applied as the basis for determining the choice of law for the parties to a contract. This paper examines the principle of good faith in the choice of law to realize justice among the parties with different laws, especially on private and public investment contracts between foreign investors and domestic investors in Indonesia, in the process of formation, implementation, or post-contract. This paper is legal research that is normative, meaning that this research is based on the prevailing laws and regulations in Indonesia. Then, the approach used is statute approach and conceptual approach. So it is expected that between the rules and the concept of existing topics will be aligned. Keywords: Choice of Law, Foreign Direct Investment Contracts, Principles of Good Faith.